Is vegetation cover in key behaviour settings important for early childhood socioemotional function? A preregistered, cross‐sectional study. Issue 3 (7th December 2021) - Mygind, Lærke; Elsborg, Peter; Schipperijn, Jasper; Boruff, Bryan; Lum, Jarrad A. G.; Bølling, Mads; Flensborg‐Madsen, Trine; Bentsen, Peter; Enticott, Peter G.; Christian, Hayley
Abstract: The environmental influences on early childhood development are understudied. The association between vegetation cover (i.e., trees, shrubs, grassed areas) in four key behaviour settings and socioemotional functioning was investigated in 1196 young children (2–5 years). Emotional difficulties were inversely associated with vegetation cover in the home yard (OR: 0.81 [0.69—0.96]) and neighbourhood (OR: 0.79 [0.67–0.94]), but not in early childhood education and care (ECEC) centre outdoor areas or the ECEC neighbourhood. The higher odds of emotional difficulties associated with lower levels of maternal education was reduced with higher percentages of home yard vegetation cover. There was no evidence of mediation of the relationship between emotional difficulties and vegetation cover by time spent playing outside the home, day or nighttime sleep duration, or physical activity. We found no associations between vegetation cover and conduct, hyperactivity and inattention, peer difficulties, or prosocial behaviours. A video abstract of this article can be viewed at https://www.youtube.com/watch?v=J3HeEiIjVZc Abstract :